Bamboo distribution in Musi Rawas District South Sumatera Province - Elyani Ami; Zulkifli Dahlan; Laila Hanum (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Indonesia is estimated to have 157 species of bamboo which is more than 10% of the world's bamboo species. Almost 50% of bamboo growth in Indonesia is endemic bamboo and more than 50% of bamboo species life in Indonesia have been utilized by the society conventionally. Further, the bamboo utilization is still having high potential to be developed by increasing the industrial development. This research aimed to investigate the diversity of the bamboo species in South Sumatera, particularly in Musi Rawas district. The result showed that in Musi Rawas district of South Sumatera province there are 10 species of bamboo located at 11 locations in protected forest area of 883.60 ha and production forest area of 177,976.26 ha. The large number of bamboo potentials viewed from various aspects and the many types of bamboo scattered in this district can be a supporting data in doing bamboo conservation efforts, especially in Musi Rawas district of South Sumatra province.